Performance Test Of Calophyllum Inophyllum Biodiesel On a Small Mono-Cylinder 5 Kva Diesel Generator - Riesta Anggarani; Cahyo S Wibowo; Maymuchar Maymuchar (Scientific Contributions Oil and Gas, 2013)
Demand of diesel fuel for villagers in rural area of Indonesia is getting higher recently. Electricity and diesel fuel shortage are forcing them to find alternative energy sources for their activities. One of the promising energy sources is Calophyllum inophyllum, which commonly grow in low-land and coastal region. In present work, methyl ester obtained from Calophyllum inophyllum were used on a 5 kVA diesel generator, pure and in 50% blend with commercial diesel fuel which also used pure as reference. A performance test cycle for each fuel was conducted with the aim of taking data of cold and warm start up time, fuel consumption, and exhaust gas emission. In the analysis of cold and warm start up time test result, it revealed that 50% blended of diesel fuel and Calophyllum inophyllum increases both cold and warm start up time when compared to pure diesel fuel and the time got higher for pure Calophyllum inophyllum biodiesel. In the result of fuel consumption, 50% blended fuel increases fuel consumption for 10.8% whereas pure biodiesel increases 16.8% fuel consumption. Analysis on the exhaust gas emission resulted that the use of Calophyllum inophyllum biodiesel and its blend decrease the CO2 emission while CO and HC emission increases. The NOx emission and the opacity of exhaust gas increase for biodiesel blend, similar results were also obtained for pure biodiesel.